Management of patients with pancreatic cystic lesions: a case-based survey - Müssle, Benjamin; Distler, Marius; Wolk, Steffen; Shrikhande, Shailesh Vinayak; Aust, Daniela E.; Arlt, Alexander; Weitz, Jürgen; Hackert, Thilo; Welsch, Thilo (Pancreatology, 2017)
Background Pancreatic cystic lesions (PCL), including intraductal papillary mucinous neoplasia (IPMN), harbor different malignant potential and the optimal management is often challenging. The present study aims to depict the compliance of experts with current consensus guidelines and the accuracy of treatment recommendations stratified by the medical specialty and hospital volume. Methods: An international survey was conducted using a set of 10 selected cases of PCL that were presented to a cohort of international experts on pancreatology. All presented cases were surgically resected between 2004 and 2015 and histopathological examination was available. Accuracy of the treatment recommendations was based on the European and international consensus guideline algorithms, and the histopathological result. Results: The response rate of the survey was 26% (46 of 177 contacted experts), consisting of 70% surgeons and 30% gastroenterologists/oncologists (GI/Onc). In the case of main-duct IPMN (MD-IPMN), surgeons preferred more often the surgical approach in comparison with the GI/Onc (55 versus 44%). The mean accuracy rate based on the European and international consensus guidelines, and the histopathological result, were 71/76/38% (surgeons), and 70/73/34% (GI/Onc), respectively. High-volume centers achieved insignificantly higher accuracy scores with regard to the histopathology. Small branch-duct IPMN with cysts <2 cm and malignant potential were not identified by the guideline algorithms. Conclusion: The survey underlines the complexity of treatment decisions for patients with PCL; less than 40% of the recommendations were in line with the final histopathology in this selected case panel. Experts and consensus guidelines may fail to predict malignant potential in small PCL.